(untitled) - Pathfinder International in Vietnam (Hà Nội, 2008)
Funded by a private donor, the Reproductive Health Projects (RHPs) was launched at a time when 89 percent of all contraceptive method clients were served by public provincial Maternal and Child Health/Family Planning facilities. There provincial facilities provided services and supported district and commune-level facilities, but though coverage was extensive, there were strong concerns about service quality.
Keywords: Medical care,Health policy,Chăm sóc y tế,Chính sách sức khoẻ